Analisis Profil Pelajar Pancasila Dimensi Bernalar Kritis pada Mata Pelajaran IPAS Fase C - Vanessa Erlita Maharani; Supianto Supianto (Universitas Sebelas Maret, 2025)
This study aims to describe the critical reasoning dimension of Pancasila student profile in the science subject phase C. The research method is quantitative descriptive. The trial subjects were 218 students in grades V and VI consisting of 4 elementary schools in Surakarta City. The result of the study showed that in general the Pancasila Student Profile in phase C with a very good category of 19%, 22% in the sufficient category, 44% in the less category, and 15% in the less category. This can be concluded that there is still a lack of the Pancasila Student Profile in the critical reasoning dimension in the science subject phase C. Kata kunci: Pancasila Student Profile, critical reasoning, science subject.